Εννοιολογική και κριτική ανάλυση των μεταφορών για τον κορονοϊό στον δημόσιο διαδικτυακό λόγο - Γαβριηλίδου Ζωή; Μητσιάκη Μαρία (Aegean Working Papers in Ethnographic Linguistics, 2022)
The COVID-19 outbreak has given rise to numerous metaphorical conceptualizations that appear to be universal. This work addresses COVID-19 metaphors in Greek public discourse as reflected in the media headlines from March 2020 up to May 2021. First, the metaphorical expressions collected are categorized according to their conceptual structures as suggested by the Extended Metaphor Theory. The most salient frame that surfaces is the COVID-19 IS WAR frame, as it does in numerous other relevant works across the world. However, the chronological analysis we attempt shows that, as time pases by, the WAR-metaphor seems to extend its scope, changing into COVID-19 WAR IS A WAR BETWEEN POLITICIANS (AND MEDICAL EXPERTS), and TRYING TO FIND THE VACCINE FOR COVID-19 IS A WAR BETWEEN NATIONS. Moreover, several other interesting mappings surface, i.e., COVID-19 IS A RACE/AN UNWELCOME GUEST/A WILD ANIMAL/A PLANET SAVIOR. Second, the Critical Metaphor Analysis employed highlights the encoders’ identities and the sociopolitical motivation of metaphor use pointing to a rhetoric of restriction and moral framing. Finally, the results underscore the urgent need to become critically aware of the persuasive power of metaphor in naturally occurring public discourse.